2021
DOI: 10.12688/gatesopenres.13457.1
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized controlled trial of the Effect of intraVenous iron on Anaemia in Malawian Pregnant women (REVAMP): Statistical analysis plan

Abstract: Background: Anaemia affects more than half of Africa’s pregnancies. Standard care, with oral iron tablets, often fails to achieve results, with compliance and gastrointestinal side-effects being a significant issue. In recent years, intravenous iron formulations have become safe, effective, and quick to administer, allowing the complete iron requirements of pregnancy to be provided in one 15-minute infusion. The Randomized controlled trial of the Effect of intraVenous iron on Anaemia in Malawian Pregnant women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The protocol and statistical analysis plan are included in the appendix (pp 11–220 ) and were published before database lock. 17 , 18 The trial was approved by ethics committees at the College of Medicine, University of Malawi, Zomba, Malawi; and The Walter and Eliza Hall Institute of Medical Research, Melbourne, VIC, Australia. All authors attest to the completeness and accuracy of the data and analyses and the adherence of the trial to the protocol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The protocol and statistical analysis plan are included in the appendix (pp 11–220 ) and were published before database lock. 17 , 18 The trial was approved by ethics committees at the College of Medicine, University of Malawi, Zomba, Malawi; and The Walter and Eliza Hall Institute of Medical Research, Melbourne, VIC, Australia. All authors attest to the completeness and accuracy of the data and analyses and the adherence of the trial to the protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Analysis followed a pre-specified statistical analysis plan. 17 Maternal and neonatal efficacy outcomes were analysed according to the randomly allocated group of the woman and included all available data, targeting the intention-to-treat principle.…”
Section: Methodsmentioning
confidence: 99%
“…Administered intravenously, it is effective in the treatment of iron deficiency anemia, delivering a replenishment dose of up to 1000 mg of iron during a minimum administration time of </= 15 min [ 13 , 14 , 15 , 16 , 17 ]. Results of several randomized trials have shown that intravenously administered FCM rapidly improves hemoglobin levels and replenishes depleted iron stores in various populations of patients with iron deficiency anemia, including those with inflammatory bowel disease [ 13 ], heavy uterine bleeding [ 14 ], postpartum iron deficiency anemia [ 15 ], heart failure [ 16 ], and chronic kidney disease [ 17 ]. It is also well tolerated in clinical trials [ 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Results of several randomized trials have shown that intravenously administered FCM rapidly improves hemoglobin levels and replenishes depleted iron stores in various populations of patients with iron deficiency anemia, including those with inflammatory bowel disease [ 13 ], heavy uterine bleeding [ 14 ], postpartum iron deficiency anemia [ 15 ], heart failure [ 16 ], and chronic kidney disease [ 17 ]. It is also well tolerated in clinical trials [ 13 , 14 , 15 , 16 , 17 ]. FCM is, therefore, an effective option in the treatment of iron deficiency anemia in patients for whom oral iron preparations are ineffective or cannot be administered.…”
Section: Introductionmentioning
confidence: 99%